The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

OS02-04 From Toxicogenomics Data to Cumulative Assessment Groups: A Framework for Chemical Grouping - S. Canzler; J. Lehmann; J. Schor; W. Busch; G. Iacono; J. Hackermüller (Toxicology Letters, 2025)

Population genetic structure in two contrasting human-altered environments of yellow pygmy rice rat Oligoryzomys flavescens - E. Muschetto; I. E. Gómez Villafañe; M. Scaltritti; J. Fraschina; V. León; L. Adduci; D. Hancke; S. Guidobono; G. R. Cueto; M. A. Tripodi; E. Hasson; M. Busch; et al. (Oecologia, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Marine Citizen Science: Current State in Europe and New Technological Developments - Carlos Garcia-Soto; Jan J. C. Seys; Oliver Zielinski; J. A. Busch; S. I. Luna; Jose Carlos Baez; C. Domegan; K. Dubsky; I. Kotynska-Zielinska; P. Loubat; Francesca Malfatti; G. Mannaerts; et al. (Frontiers in Marine Science, 2021)
Marine citizen science is emerging with promising opportunities for science, policy and public but there is still no comprehensive overview of the current state in Europe. Based on 127 projects identified for the North Sea area we estimate there might be as much as 500 marine and coastal citizen science projects running in Europe, i.e., one marine citizen science project per ∼85 km of coastline, with an exponential growth since 1990. Beach-based projects are more accessible and hence most popular (60% of the projects), and the mean duration of the projects is 18–20 years. Current trends, topics, organizers, aims, and types of programme in terms of participation are presented in this overview. Progress in marine citizen science is specially enabled and promoted through technological developments. Recent technological advances and best practise examples are provided here, untapping the potential of smart mobile apps, do-it-yourself (DIY) technologies, drones, and artificial intelligence (AI) web services.

Ocean and coastal indicators: understanding and coping with climate change at the land-sea interface - Patricia M. Clay; Jennifer Howard; D. Shallin Busch; Lisa L. Colburn; Amber Himes-Cornell; Steven S. Rumrill; Stephani G. Zador; Roger B. Griffis (Climatic Change, 2020)

The association of children’s mathematic abilities with both adults’ cognitive abilities and intrinsic fronto-parietal networks is altered in preterm-born individuals - J. G. Bäuml; C. Meng; M. Daamen; N. Baumann; B. Busch; P. Bartmann; D. Wolke; H. Boecker; A. Wohlschläger; C. Sorg; Julia Jaekel (Brain Structure and Function, 2017)

Extensive and interrelated subcortical white and gray matter alterations in preterm-born adults - C. Meng; J. G. Bäuml; M. Daamen; J. Jaekel; J. Neitzel; L. Scheef; B. Busch; N. Baumann; H. Boecker; C. Zimmer; P. Bartmann; D. Wolke; et al. (Brain Structure and Function, 2016)

Increased mortality associated with extreme-heat exposure in King County, Washington, 1980–2010 - Tania Busch Isaksen; Richard A. Fenske; Elizabeth K. Hom; You Ren; Hilary Lyons; Michael G. Yost (International Journal of Biometeorology, 2016)

Atlantic salmon, S almo salar L . are broadly susceptible to isolates representing the N orth A merican genogroups of infectious hematopoietic necrosis virus - G Kurath; J R Winton; O B Dale; M K Purcell; K Falk; R A Busch (Journal of Fish Diseases, 2016)
Beginning in 1992, three epidemic waves of infectious hematopoietic necrosis, often with high mortality, occurred in farmed A tlantic salmon S almo salar L . on the west coast of N orth A merica. We compared the virulence of eleven strains of infectious hematopoietic necrosis virus ( IHNV ), representing the U , M and L genogroups, in experimental challenges of juvenile A tlantic salmon in freshwater. All strains caused mortality and there was wide variation within genogroups: cumulative mortality for five U ‐group strains ranged from 20 to 100%, four M ‐group strains ranged 30‐63% and two L ‐group strains varied from 41 to 81%. Thus, unlike P acific salmonids, there was no apparent correlation of virulence in a particular host species with virus genogroup. The mortality patterns indicated two different phenotypes in terms of kinetics of disease progression and final per cent mortality, with nine strains having moderate virulence and two strains (from the U and L genogroups) having high virulence. These phenotypes were investigated by histopathology and immunohistochemistry to describe the variation in the course of IHNV disease in A tlantic salmon. The results from this study demonstrate that IHNV may become a major threat to farmed A tlantic salmon in other regions of the world where the virus has been, or may be, introduced.

Oxygen minimum zones harbour novel viral communities with low diversity - Noriko Cassman; Alejandra Prieto‐Davó; Kevin Walsh; Genivaldo G. Z. Silva; Florent Angly; Sajia Akhter; Katie Barott; Julia Busch; Tracey McDole; J. Matthew Haggerty; Dana Willner; Gadiel Alarcón; et al. (Environmental Microbiology, 2012)
Summary Oxygen minimum zones ( OMZs ) are oceanographic features that affect ocean productivity and biodiversity, and contribute to ocean nitrogen loss and greenhouse gas emissions. Here we describe the viral communities associated with the E astern T ropical S outh P acific ( ETSP ) OMZ off I quique, C hile for the first time through abundance estimates and viral metagenomic analysis. The viral‐to‐microbial ratio ( VMR ) in the ETSP OMZ fluctuated in the oxycline and declined in the anoxic core to below one on several occasions. The number of viral genotypes (unique genomes as defined by sequence assembly) ranged from 2040 at the surface to 98 in the oxycline, which is the lowest viral diversity recorded to date in the ocean. Within the ETSP OMZ viromes, only 4.95% of genotypes were shared between surface and anoxic core viromes using reciprocal BLASTn sequence comparison. ETSP virome comparison with surface marine viromes ( S argasso S ea, G ulf of M exico, K ingman R eef, C hesapeake B ay) revealed a dissimilarity of ETSP OMZ viruses to those from other oceanic regions. From the 1.4 million non‐redundant DNA sequences sampled within the altered oxygen conditions of the ETSP OMZ , more than 97.8% were novel. Of the average 3.2% of sequences that showed similarity to the SEED non‐redundant database, phage sequences dominated the surface viromes, eukaryotic virus sequences dominated the oxycline viromes, and phage sequences dominated the anoxic core viromes. The viral community of the ETSP OMZ was characterized by fluctuations in abundance, taxa and diversity across the oxygen gradient. The ecological significance of these changes was difficult to predict; however, it appears that the reduction in oxygen coincides with an increased shedding of eukaryotic viruses in the oxycline, and a shift to unique viral genotypes in the anoxic core.

Mycoplasma contamination of murine embryonic stem cells affects cell parameters, germline transmission and chimeric progeny - Kyriaki Markoullis; Diana Bulian; Gabriele Hölzlwimmer; Leticia Quintanilla-Martinez; Katrin-Janine Heiliger; Horst Zitzelsberger; Hagen Scherb; Josef Mysliwietz; Cord C. Uphoff; Hans G. Drexler; Thure Adler; Dirk H. Busch; et al. (Transgenic Research, 2009)

“Technically Unavoidable” in Terms of Genetically Modified Organisms – an Approach for Food Control - H.-U. Waiblinger; N. Graf; D. Mäde; K. Woll; U. Busch; B. Holland; H. Pilsl; G. Naeumann; R. Reiting; B. Ehrentreich; M. Schulze; B. Tschirdewahn; et al. (Journal of Consumer Protection and Food Safety, 2007)

Effects of the atrial antiarrhythmic drug AVE0118 on cardiac ion channels - Heinz Ggelein; J. Brendel; K. Steinmeyer; C. Strbing; N. Picard; D. Rampe; K. Kopp; A.E. Busch; M. Bleich (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Epidemiology of rubella infections in Austria: important lessons to be learned - B. Falkensammer; G. Walder; D. Busch; A. Gieauf; M. Dierich; R. Wrzner (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Inhibitors of ATP-sensitive potassium channels in guinea pig isolated ischemic hearts - A. Weyermann; H. Vollert; A. E. Busch; M. Bleich; H. Ggelein (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Granulocyte colony-stimulating factor (G-CSF) reduces not only gram-negative but also gram-positive infection-associated proinflammatory cytokine release by interaction between Kupffer cells and leukocytes - G. A. Wanner; C. J. Busch; B. Vollmar; M. D. Menger (Inflammation Research, 2004)

Infilling of the Younger Kathmandu–Banepa intermontane lake basin during the Late Quaternary (Lesser Himalaya, Nepal): a sedimentological study - H. G. Dill; D. R. Khadka; R. Khanal; R. Dohrmann; F. Melcher; K. Busch (Journal of Quaternary Science, 2003)
The Kathmandu and Banepa Basins, Central Nepal, are located in a large syncline of the Lesser Himalayas. The Older Kathmandu Lake evolved during the Pliocene and early Pleistocene; the Younger Kathmandu Lake, which is the focus of this study, is infilled with late Quaternary sediments. Three formations, arranged in stratigraphical order, the Kalimati, Gokarna and Thoka Formations formed during the infilling stage of this lacustrine basin. Structural and textural sedimentological analyses, a chemical survey across the basin and mineralogical investigations of fine‐grained sediments form the basis of this palaeogeographical study. The basin under investigation was covered by a perennial freshwater lake before 30 000 yr BP. The lake was infilled with alluvial and fluvial sediments delivered mainly from the mountains north of the basin. A fairly low gradient was favourable for the formation of diatomaceous earths, carbonaceous mudstones and siltstones, which were laid down in the centre of the lake and in small ponds. Towards the basin edge, lacustrine sediments gave way to deltaic deposits spread across the delta plain. Crevasse splays and anastomosing rivers mainly delivered suspended load for the widespread siltstones and mudstones. The proximal parts of the alluvial–fluvial sedimentary wedge contain debris flows that interfinger with fine‐grained floodplain deposits. Three highstands of the water‐level (>30 000 yr BP, 28 000–19 000 yr BP, 11 000–4000 yr BP (?)) have been recognised in the sedimentary record of the younger Kathmandu Lake in the Late Quaternary. Second‐order water‐level fluctuations are assumed to be triggered by local processes (damming by tectonically induced landslides). First‐order water‐level fluctuations are the result of climatic changes. Copyright © 2003 John Wiley & Sons, Ltd.

Dependence of I Ks biophysical properties on the expression system - Seebohm G.; Lerche C.; Busch A.; Bachmann A. (Pflügers Archiv - European Journal of Physiology, 2001)

Effect of urea and osmotic cell shrinkage on Ca2+ entry and contraction of vascular smooth muscle cells - C.A. Wagner; S.M. Huber; S. Wärntges; G. Zempel; N.K. Kaba; R. Fux; N. Orth; G.L. Busch; S. Waldegger; I. Lambert; B. Nilius; H. Heinle; et al. (Pflügers Archiv - European Journal of Physiology, 2000)

Degradation of desferrioxamines by Azospirillum irakense: Assignment of metabolites by HPLC/electrospray mass spectrometry - G. Winkelmann; B. Busch; A. Hartmann; G. Kirchhof; R. Süßmuth; G. Jung (BioMetals, 1999)

MHC class I restricted T cell responses tolisteria monocytogenes, an intracellular bacterial pathogen - Alyce Finelli; Kristen M. Kerksiek; S. Elise Allen; Natalia Marshall; Roberto Mercado; Ingrid Pilip; Dirk H. Busch; Eric G. Pamer (Immunologic Research, 1999)

Molecular and functional characterization of s-KCNQ1 potassium channel from rectal gland of Squalus acanthias - Siegfried Waldegger; Bernd Fakler; Markus Bleich; Petra Barth; Anna Hopf; U. Schulte; Andreas E. Busch; Stephen G. Aller; John N. Forrest Jr.; Rainer Greger; Florian Lang (Pflügers Archiv - European Journal of Physiology, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Structural rearrangement in chromosome 2M of Aegilops comosa has prevented the utilization of the Compair and related wheat-Ae. comosa translocations in wheat improvement - S. Nasuda; B. Friebe; W. Busch; R. G. Kynast; B. S. Gill (Theoretical and Applied Genetics, 1998)

Lack of interaction between meloxicam and warfarin in healthy volunteers - D. Türck; C. A. P. F. Su; G. Heinzel; U. Busch; E. Bluhmki; J. Hoffmann (European Journal of Clinical Pharmacology, 1997)

Potato seed-piece treatment in Ontario - L. V. Busch; R. G. Rowberry (American Journal of Potato Research, 1972)

Chemical control of common scab of potato - L. V. Busch; G. C. Ashton (American Journal of Potato Research, 1964)

ber die Zusammensetzung von Involutionsformen der Mikroorganismen - A. Rippel-Baldes; G. Busch; F. Radler (Archives of Microbiology, 1956)